1984
DOI: 10.1001/archinte.144.5.967
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile. Colonization and toxin production in a cohort of patients with malignant hematologic disorders

Abstract: We examined 45 (80%) of 56 consecutive adult patients with malignant hematologic disorders who were hospitalized during a 15-week period at Emory University Hospital, Atlanta. Stool samples for Clostridium difficile culture and cytotoxin assay were obtained on admission and then weekly during each patient's hospitalization. On admission, four patients had detectable C difficile in their stool samples, which was associated with prior antimicrobial use but not with prior cancer chemotherapy. One of the four pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…J. Cancer (I 992), 66, 666 667 Discussion The contribution of Clostridium difficile as a cause of diarrhoea in patients with malignant diseases as reported by others (Cudmore et al, 1982;Morris et al, 1984;Miller & Koornhof, 1984;Rampling et al, 1985;Heard et al, 1988) was confirmed by the present study. However, most reports have dealt with description of single patients (Cudmore et al, 1982;Miller & Koornhof, 1984;Rampling et al, 1985;Fainstein et al, 1981), and only few studies have produced estimation of the incidence/prevalence of this infection in a prospectively manner (Morris et al, 1984;Heard et al, 1988).…”
Section: Methodssupporting
confidence: 84%
See 2 more Smart Citations
“…J. Cancer (I 992), 66, 666 667 Discussion The contribution of Clostridium difficile as a cause of diarrhoea in patients with malignant diseases as reported by others (Cudmore et al, 1982;Morris et al, 1984;Miller & Koornhof, 1984;Rampling et al, 1985;Heard et al, 1988) was confirmed by the present study. However, most reports have dealt with description of single patients (Cudmore et al, 1982;Miller & Koornhof, 1984;Rampling et al, 1985;Fainstein et al, 1981), and only few studies have produced estimation of the incidence/prevalence of this infection in a prospectively manner (Morris et al, 1984;Heard et al, 1988).…”
Section: Methodssupporting
confidence: 84%
“…However, most reports have dealt with description of single patients (Cudmore et al, 1982;Miller & Koornhof, 1984;Rampling et al, 1985;Fainstein et al, 1981), and only few studies have produced estimation of the incidence/prevalence of this infection in a prospectively manner (Morris et al, 1984;Heard et al, 1988). Acute leukaemias were identified as increasing the risk of infection (Morris et al, 1984;Heard et al, 1988), whereas no data are available for patients with solid tumours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…C. difficile was identified by Hall and O'Toole abdominal pain (80-90%) [5,21,22,[51][52][53][54][55][56]. The severity of diarrhea may vary from mild diarrhea that resolves as [24] in 1935.…”
Section: Historical Background and General Aspectsmentioning
confidence: 99%
“…Although we do not have similar comparisons with regards to rates per antibiotic usage, the high identification of C difficile in our NAD and CAD populations may reflect a high baseline rate of antibiotic usage, good detection techniques for C difficile or differences in our population in terms of food preparation and consumption. Similarly, patients with malignant disease receiving chemotherapy have been noted to be at risk for C difficile infection because of the numerous courses of antibiotics that they receive and because cancer chemotherapy itself may predispose patients to gut colonization with C difficile (53)(54)(55)(56). CAD episodes in which bacterial pathogens were isolated were predominantly in children older than five years of age.…”
Section: Discussionmentioning
confidence: 99%